2013
DOI: 10.1186/1550-2783-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fed- versus fasted state resistance training during Ramadan on body composition and selected metabolic parameters in bodybuilders

Abstract: BackgroundMuslim bodybuilders often continue training during Ramadan. However, the effect of resistance training in a fasted versus a fed state during Ramadan on body composition and metabolic parameters in bodybuilders is not well known. The aim of this study was to evaluate the effects of resistance training in a fasted versus a fed state during Ramadan on body composition and metabolic parameters in bodybuilders.MethodsSixteen men were allocated to two groups: Eight practicing resistance training in the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 32 publications
1
43
0
2
Order By: Relevance
“…28,29 We found no significant decrease in body fat, but visceral fat decreased significantly after the fasting of Lent. A significant decrease in fat mass was found at the end of Ramadan by Trabelsi et al 30 In present study the decrease in body weight is accompanied by non-significant decreases in fat free mass and fat mass. The results found on the parameters of body composition could be related to diet.…”
Section: Discussionsupporting
confidence: 55%
“…28,29 We found no significant decrease in body fat, but visceral fat decreased significantly after the fasting of Lent. A significant decrease in fat mass was found at the end of Ramadan by Trabelsi et al 30 In present study the decrease in body weight is accompanied by non-significant decreases in fat free mass and fat mass. The results found on the parameters of body composition could be related to diet.…”
Section: Discussionsupporting
confidence: 55%
“…Compared to pre-and post-Ramadan, six studies indicated that daily energy intakes remained similar during Ramadan (14,(21)(22)(23)(24)(25). However, three studies showed a decrease of energy intake (26-28).…”
Section: Energy Intakementioning
confidence: 99%
“…The duration of the daytime fast varies and is significantly impacted by the location and season. The typical fasting duration is generally 10 h, but can exceed 18 h [57][58][59][60][61][62]. A longer daylight period is found at extreme latitudes, and for these extreme fasting durations, some religious exceptions may apply [63].…”
Section: Ramadan Intermittent Fastingmentioning
confidence: 99%